Comparing violence in schizophrenia patients with and without comorbid substance‐use disorders to community controls. (4th February 2013) - Short, T.; Thomas, S.; Mullen, P.; Ogloff, J. R. P.
<x xml:space="preserve">Abstract</x> Objective This study examined crime and violence in patients with schizophrenia with and without comorbid substance‐use disorders. Method A case‐linkage design was used to compare patterns of violence and offending between 4168 schizophrenia patients drawn from a state‐wide public mental health register, both with and without comorbid substance‐use disorders, and a randomly selected community control group who had never been diagnosed with schizophrenia. Results Schizophrenia patients were significantly more likely than controls to be guilty of violent and non‐violent offences, and to have been involved in family violence. Even schizophrenia patients without comorbid substance‐use disorders had a significantly elevated risk of violence; this group were more than twice as likely as controls to have a violent conviction. The elevation of violence risk in schizophrenia patients was higher in females (OR = 8.59) than males (OR = 2.25). Conclusion The increased risk of violent offending in schizophrenia cannot be solely attributed to the effects of comorbid substance misuse, although comorbidity certainly heightens the likelihood of criminality. In addition to offending, people with schizophrenia are more likely than community controls to come to the attention of police via their involvement in family violence incidents. Schizophrenia is a particularly strong risk factor for violence in females.